Lapicotton technique in the treatment of progressive collapsing foot deformity - de Cesar Netto, Cesar; Ahrenholz, Samuel; Iehl, Caleb; Vivtcharenko, Victoria; Schmidt, Eli; Lee, Hee; Dibbern, Kevin; Mansur, Nacime (Journal of the Foot & Ankle, 2020)
We present a technical surgical description of a 36-year-old female diagnosed with Progressive Collapsing Foot Deformity (PCFD) treated with a medial displacement calcaneus osteotomy, a lateral column lengthening, and a modified Lapidus fusion. In order to increase the plantar flexion power of this arthrodesis and minimize the loss in ray length with joint preparation, a bone block structured graft was used. Fixation was performed using a post implant in the medial cuneiform with crossing screws though the surfaces and the graft. Forefoot varus was properly corrected intraoperatively by using the described surgical technique. Satisfactory functional short-term results and an excellent alignment was accomplished. Level of Evidence V; Therapeutic Studies; Expert Opinion.